Log-transformed B-type natriuretic peptide as a prognostic predictor in patients undergoing cardiovascular surgery. Issue 12 (December 2018) - Takagi, Sho; Machida, Yuichiro; Kobata, Takashi; Sakamoto, Daisuke; Sakamoto, Shigeru; Kanda, Tsugiyasu
Objective: This study was performed to explore the association between circulating B-type natriuretic peptide (BNP) and other mortality-related factors in patients undergoing cardiovascular surgery. Methods: In this observational study, multilevel linear regression analysis and multilevel survival analysis were performed to measure the log-transformed BNP (lnBNP) value at four time points in 197 patients with 788 repeated data measurements. Effects of the interaction between the time points and the two intervention groups (cardiac surgery and vascular surgery) were also investigated. Six models were evaluated to identify the best fit for the data. Stata/MP® version 14.2 (Stata Corp., College Station, TX, USA) was used to analyze the two-level variance component model fitting. Results: There were significant differences in the fixed-effect parameters of lnBNP, such as the time point, age, body mass index, emergency operation, prognostic nutritional index, and estimated glomerular filtration rate. According to the multilevel survival analysis for all-cause death and vascular death, lnBNP significantly differed and was a common prognostic marker. Conclusion: As lnBNP increased by 1 point, all-cause death increased 2.07 times and vascular death increased 3.10 times. lnBNP is an important prognostic predictor and quantitative biochemical marker in patients undergoing cardiovascular surgery.